The 2005 General Elections in Thailand: Toward a One-Party Government - Nogsuan, Siripan (Kasarinlan: Philippine Journal of Third World Studies; Vol 20 No 1 (2005): Electoral Politics 2, 2007)
Thailand’s 1997 Constitution and the new electoral system make it easier for big money to take control over Thailand’s party politics. Some of the political trends that have emerged in the 2005 general elections in Thailand prove this assertion. These trends include the increased importance of party labels and leaders in electoral politics, the widening role of the mass media in elections, the professionalization of the electoral campaign, the use of the policy platform as a vote-getting tool, and the continuation of money politics and vote buying. The dominance of the Thai Rak Thai (Thai Loves Thai [TRT]) exemplifies these trends. As a single-party government, TRT will no longer have to worry about coalition disharmony and fragmented government. However, the stability of the government still largely depends on the deft handling of the rival factions within Thai Rak Thai. More significantly, the success of one party in electoral politics does not necessarily translate into democratic consolidation.
Keywords: Thailand; election; political party; Thaksin Shinawatra; Thai Rak Thai; democratic consolidation